Synthesis of Silver Nanoparticles using Red Algae, Characterization and Effect on Beneficial Soil Microbes - Murugammal, V.; Flora, G. (Asian Journal of Biological and Life Sciences, 2017)
The synthesis and characterization and application of biologically synthesised nanomaterials are important aspect in nanotechnology. The present study focused on the synthesis of silver nanoparticles using red algae characterization and effect on beneficial soil microbes. The formation of AgNPs were performed by UV-Visible spectrophotometer revealed surface plasmon resonance at 420nm .The structure and size distribution of the silver nanoparticles were examined by Transmission Electron Microscopy (TEM) which showed that the particles are spherical in shape with size ranging from 50nm. Finally the compounds responsible for the silver nanoparticles biosynthesis were studied using Fourier Transmission-Infrared (FT-IR) spectroscopy analysis showed that the synthesised nano-Ag was capped with bimolecular compounds which are responsible for reduction of silver ions. Moreover the microbes isolated from garden soil of synthesised silver nanoparticles exhibited potential inhibitory activity against ten tested microbes showed that (Bacillus spp, Bacillus substilis, Staphyllococcus epidermidis, Serratia spp, Pseudomonas fluorescens, Pseudomonas spp, Aspergillus flavus, Aspergillus fumigates, Alternaria altermata, Cladosporium spp).
Keywords: Antioxidant activity; FT-IR; Marine macroalgae -Rhodymenia palmata; Silver nanoparticles; Soil microbes; TEM and UV- Vis